2023
DOI: 10.1007/s11192-023-04679-5
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic positivity in soft and hard disciplines: temporal dynamics, disciplinary variation, and the relationship with research impact

Abstract: Previous studies have investigated the use of positive/negative language in academic discourse, and have found a tendency toward using more positive language in academic writing. However, little is known about whether the features and dynamics of linguistic positivity vary across disciplines. In addition, the relationship between linguistic positivity and research impact deserves further evaluation. To address these issues, the present study investigated linguistic positivity in academic writing from a cross-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…These include basic textual features, such as paper metadata (Ma et al, 2021) and paper length (Haustein et al, 2015;Xie et al, 2019). Additionally, more refined textual analyses have been proposed as citation predictors, encompassing linguistic complexity and readability metrics (Ante, 2022;Lu et al, 2019;Sienkiewicz & Altmann, 2016), stylometry of titles and abstracts (Jimenez et al, 2020), and sentiment analysis (Liu & Zhu, 2023). In a review regarding the application of artificial intelligence for predicting citations and other research assessment metrics, Kousha and Thelwall (2022) observed that the existing predictors, such as readability scores and text-based analyses, have inconsistent predictive power.…”
Section: Introductionmentioning
confidence: 99%
“…These include basic textual features, such as paper metadata (Ma et al, 2021) and paper length (Haustein et al, 2015;Xie et al, 2019). Additionally, more refined textual analyses have been proposed as citation predictors, encompassing linguistic complexity and readability metrics (Ante, 2022;Lu et al, 2019;Sienkiewicz & Altmann, 2016), stylometry of titles and abstracts (Jimenez et al, 2020), and sentiment analysis (Liu & Zhu, 2023). In a review regarding the application of artificial intelligence for predicting citations and other research assessment metrics, Kousha and Thelwall (2022) observed that the existing predictors, such as readability scores and text-based analyses, have inconsistent predictive power.…”
Section: Introductionmentioning
confidence: 99%